2015
DOI: 10.18632/oncotarget.6714
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Notch to overcome radiation resistance

Abstract: Radiotherapy represents an important therapeutic strategy in the treatment of cancer cells. However, it often fails to eliminate all tumor cells because of the intrinsic or acquired treatment resistance, which is the most common cause of tumor recurrence. Emerging evidences suggest that the Notch signaling pathway is an important pathway mediating radiation resistance in tumor cells. Successful targeting of Notch signaling requires a thorough understanding of Notch regulation and the context-dependent interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 202 publications
(207 reference statements)
2
44
0
Order By: Relevance
“…In our study, PyClone analysis suggested that cells harboring NOTCH1 mutations were sensitive to radiation, whereas those harboring EGFR and MGA mutations were resistant to radiation. Recent studies suggest that activation of the NOTCH signaling pathway is related to radiation resistance in tumor cells (19)(20)(21). OncodriveROLE, a machine learning-based approach, indicated that the NOTCH1 p.Cys1374Tyr mutation, as detected in our study, is a "loss-of-function" mutation (22,23).…”
Section: Discussionsupporting
confidence: 63%
“…In our study, PyClone analysis suggested that cells harboring NOTCH1 mutations were sensitive to radiation, whereas those harboring EGFR and MGA mutations were resistant to radiation. Recent studies suggest that activation of the NOTCH signaling pathway is related to radiation resistance in tumor cells (19)(20)(21). OncodriveROLE, a machine learning-based approach, indicated that the NOTCH1 p.Cys1374Tyr mutation, as detected in our study, is a "loss-of-function" mutation (22,23).…”
Section: Discussionsupporting
confidence: 63%
“…γ-secretase inhibitors (GSI) effectively inhibit the NOTCH pathway in basic and pre-clinical research as well as clinical trials [1314]. Inhibition of NOTCH signaling in glioma stem cells has been shown to impair the tumorigenic capacity of these cells and enhance their radiation and chemo-sensitivity [1518]. Importantly, NOTCH inhibition has also been linked to TMZ-resistance through the EGF containing fibulin-like extracellular matrix protein 1 (EFEMP1) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Notch signaling substantially impacts tumor initiation, progression, and treatment response, and combining Notch therapeutics with radiotherapy may result in synergistic improvements in various cancers, including cutaneous squamous cell carcinomas (SCCs) . Radio‐resistance is a great obstacle for NPC management .…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway is of significance in modulating cell fates, including cell proliferation and cell differentiation . New evidence indicated that the Notch signaling pathway plays an important role in mediating radiotherapy resistance of tumor cells, such as brain, lung and breast tumors . The Notch signaling pathway is also identified as a cancer therapeutic target in renal cell carcinoma, gastric cancer, and breast cancer given its self‐renewal and differentiation in tumor cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation